On the method of teaching russian accent in polish schools - Olechnowicz, Mścisław (Glottodidactica, 1966)
Having analysed the results of teaching in experimental groups and types of mistakes made by students, the author suggests that the methods of teaching Russian accent should be based on: making students acquainted, particularly the older ones, with the norms and structure of Russian accent during the whole process of teaching; developing students’ perception abilities and their auditory memory with the help of special drills based on mechanical aids of teaching; analysing and comparing the characteristic features of Russian and Polish accents in order to eliminate the influence of the mother tongue. It has been experimentally proved that teaching Russian accent by means of its norms effectively helps students to master the correct Russian pronunciation and to acquire orthoepic habits.